(untitled) - Albin, Stephan (Indianapolis, Ind., 2003)
This innovative book uncovers all the steps readers should follow in order to build successful software and systems * With the help of numerous examples, Albin clearly shows how to incorporate Java, XML, SOAP, ebXML, and BizTalk when designing true distributed business systems * Teachers how to easily integrate design patterns into software design * Documents all architectures in UML and presents code in either Java or C++
Keywords: Software architecture,Cấu trúc phần mềm